Magnetic resonance spectroscopy in cervical spondylotic myelopathy: a systematic review of metabolite changes and clinical correlations - Montes-González, Iris Tatiana; Griswold, Dylan Paul; Peralta-Pizza, Fernando; Israel-Romero, José Alberto; Mier-García, Juan Felipe; Soriano-Sanchez, José Antonio (Frontiers in Medicine, 2025)
IntroductionCervical spondylotic myelopathy (CSM) is a common degenerative condition characterized by narrowing of the cervical spinal canal, leading to progressive spinal cord injury and functional decline. While magnetic resonance imaging (MRI) is the gold standard for diagnosing CSM, it has limitations in predicting clinical outcomes. Magnetic resonance spectroscopy (MRS) offers metabolic insights that may enhance diagnostic and prognostic capabilities in CSM.MethodsWe conducted a systematic review following the PRISMA guidelines. Comprehensive literature searches were performed in PubMed, OVID, EMBASE, Web of Science, and the Cochrane Central Register of Controlled Trials up to June 2023. Studies included human subjects with CSM, a cohort of at least 10 patients, and reported primary data on cervical spine MRS findings correlated with clinical scales such as the modified Japanese Orthopaedic Association (mJOA) scale, both pre- and post-operatively.ResultsSix prospective studies involving 123 patients (average age 45.8 to 63 years) met the inclusion criteria. Common symptoms were neck pain, radicular upper-limb pain, paresthesia, and motor impairment. MRS findings indicated that symptomatic CSM patients had reduced N-acetyl aspartate to creatine (NAA/Cr) ratios and elevated choline to creatine (Cho/Cr) and choline to NAA (Cho/NAA) ratios compared to healthy controls. Lactate peaks were detected in a significant proportion of symptomatic patients, suggesting hypoxic or inflammatory injury. Decreased NAA/Cr and increased Cho/NAA ratios correlated with lower mJOA scores, indicating more severe myelopathy. Post-operative increases in NAA/Cr ratios and decreases in Cho/NAA ratios were associated with improved mJOA scores, highlighting the prognostic value of these metabolites.ConclusionMRS provides valuable metabolic information correlating with clinical severity and functional outcomes in CSM. Reduced NAA/Cr and elevated Cho/Cr and Cho/NAA ratios are associated with more severe disease and may predict surgical recovery. MRS shows promise as a non-invasive tool for enhancing the diagnosis and management of CSM. Further research is needed to standardize protocols, validate findings in larger cohorts, and integrate MRS into clinical practice.